Characterization of the Maize Stalk Rot Pathogens Fusarium subglutinans and F. temperatum and the Effect of Fungicides on Their Mycelial Growth and Colony Formation - Jong-Hwan Shin; Joon-Hee Han; Ju Kyong Lee; Kyoung Su Kim (The Plant Pathology Journal, 2014)
Maize is a socioeconomically important crop in many countries. Recently, a high incidence of stalk rot disease has been reported in several maize fields in Gangwon province. In this report, we show that maize stalk rot is associated with the fungal pathogens Fusarium subglutinans and F. temperatum. Since no fungicides are available to control these pathogens on maize plants, we selected six fungicides (tebuconazole, difenoconazole, fluquinconazole, azoxystrobin, prochloraz and kresoxim-methyl) and examined their effectiveness against the two pathogens. The in vitro antifungal effects of the six fungicides on mycelial growth and colony formation were investigated. Based on the inhibition of mycelial growth, the most toxic fungicide was tebuconazole with 50% effective concentrations (EC₅₀) of <0.1 μg/ml and EC₉₀ values of 0.9 μg/ml for both pathogens, while the least toxic fungicide was azoxystrobin with EC₅₀ values of 0.7 and 0.5 μg/ml for F. subglutinans and F. temperatum, respectively, and EC₉₀ values of >3,000 μg/ml for both pathogens. Based on the inhibition of colony formation by the two pathogens, kresoxim-methyl was the most toxic fungicide with complete inhibition of colony formation at concentrations of 0.1 and 0.01 μg/ml for F. subglutinans and F. temperatum, respectively, whereas azoxystrobin was the least toxic fungicide with complete inhibition of colony formation at concentrations >3,000 μg/ml for both pathogens.